The rational imagination : how people create alternatives to reality - Byrne, Ruth M.J. (Cambridge, Mass. : MIT, 2007)
1 The Counterfactual ##2 Imagination and Rational ##3 Imagining How Actions Might Have Been ## 4 Thinking about What Should Have Happened ## 5 Causal Relations and Counterfactuals##6 "Even If ..."##7 The "Last Chance"##8 Individuals and Creative Thought##9 The Idea of a Rational Imagination
"A Bradford book". Originally published: 2005.
boek